Ethnic Movement in Nepal: Interactions Between State and Non-State Actors - Kaini, Tika Raj; Rai, Menu (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
This paper aims to explore the nature and role of ethnic movements taken place in Nepal. It basically highlights the pattern of interactions between state and non-state actors participated in ethnic movements. In the backdrop of the essence of rise and extent of influence, authors have explored the result experienced by the participants in this movement. It has further depicted the realms of change induced in the causation of ethnic movement. Trajectories of movements, forms of these movement, focus of movements and the collectivity generated in movement have also been investigated here in this paper.